Mergers and Acquisition in the Iron and Steel Sector Based in UK and US. - Bagaria, Sonal (2008)
From the past few year, Mergers and Acquisitions (M&A) have ruled the environment in which the companies function. Many researchers have also been carried out where the main focus of the study is on the abnormal returns of the acquirers of the firm after the merger. The results have discovered that on average, the returns to the target companies are positive and that they gain from mergers. However, the bidder returns may be zero or negative, but it still remains a puzzle if they gain from mergers in the long run. This research studies the performance of mergers and acquisitions and its influence on the returns of the acquirers of the firm. It considers a sample size of 51 companies covering UK and US in iron and steel sector and studies the performance of companies after merger and acquisition. Here use the event study with market model approach to test the profitability of the merger.